PENYUSUAN DALAM PEMIKIRAN PAKAR (Studi Penalaran Hukum Berwawasan Fiqh Indonesia) - Ahmad, La Ode Ismail (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2016)
Giving exclusive breastfeeding, in Islamic perspective, discusses about the milk (al-labn) coming out from the women breast, the status of giving exclusive breastfeeding to the children as a job, the children right to get the good milk, the responsibility of parent to take care, and the social implication of the exclusive breastfeeding. This is because that mother breastfeeding ¬-the same as blood- is the liquid in women body affecting the history of social human. If the blood can keep the brotherhood, the breastfeeding can keep the unity and the harmony of family. These, have the similarity implicative relation in descent rotation.